Crystallization process of meenamic acid : optimization, molecular dynamics simulations and PAT (Process Analytical Technology) implementation - Siti Kholijah binti Abdul Mudalip (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Mefenamic acid [(2-(2, 3-dimethylphenyl)aminobenzoic acid] is a commonly used non-steroidal anti-inflammatory drug (NSAID) for management of pain caused by menstrual disorders. Crystallization of an active pharmaceutical ingredients (APIs) such as mefenamic acid, those exist in a different polymorphic forms, morphology, and crystal size distributions (CSD) remain a significant challenge in the pharmaceutical industries. This work presents the application of molecular modelling and cheap in-line Process Analytical Technology (PAT) tools in the development of the pharmaceutical crystallization process. The solvent screening was performed to investigate the effect of different classes of solvents, namely polar protic (water, ethanol and propanol), dipolar aprotic (N,N-dimethylacetamide (DMA), N,N-dimethylformamide (DMF), ethyl acetate (EA), and propanone), and apolar aprotic (hexane, heptane, and cyclohexane) on the mefenamic acid solubility, polymorphism and morphology. For estimation of the metastable zone width (MSZW) and nucleation kinetic parameters, the crystallization experiments were performed using a polythermal method at different cooling rates and initial concentrations. In this method, the in-line conductivity system was introduced as a tool for in-line detection of nucleation events in addition to turbidity system. Furthermore, sequential optimization strategy using one-factor-at-a-time (OFAT) and face-centred-central-composite design (FCCCD) were performed at different cooling rates, initial concentrations and crystallization times to improve the crystals aspect ratio and CSD. The Conductor-Like Screening Model for Real Solvents (COSMO-RS) was used to predict the solubility values. Whereas, a molecular dynamics simulation was performed in Material Studio software to model the mefenamic acid behaviour in different solvents. The experimental study shows that mefenamic acid solubility was high in dipolar aprotic solvents, moderate in polar protic solvents (ethanol and propanol), and poor in apolar aprotic solvents and water. The crystallization of mefenamic acid using DMA, EA, acetone, ethanol and propanol produce Form I (needle-like), while DMF produces Form II (cubic). The MSZW of selected solvent system (EA) was increased with the increase of cooling rates and decreased with the increase of saturation concentration. The highest solution concentration which was 3.6 g/ 100 g ethyl acetate, shows highest nucleation rate constant, k_n (0.1460) and lowest nucleation order, n (4.1374) values. The polymorphic form of mefenamic acid is Form I. The OFAT and optimization results show that initial solution concentrations, cooling rates, and crystallization time highly influent the crystals aspect ratio and CSD. The developed model is adequately fitted with the experimental data as the determination coefficient (R2) of 0.9993 is in a reasonable agreement with the adjusted R2 of 0.9980. The minimum aspect ratio of 9.51 with narrower CSD was obtained with solution concentration of 1.65 g/ 100 g ethyl acetate, cooling rate of 0.8 ºC/min, and crystallization time of 11 min. The predicted solubility values using COSMO-RS concur very well with the experimental values with an average deviation less than 10%. The results of the molecular dynamics simulation show that the density, diffusion coefficient and radial distribution functions (RDFs) calculated for each solvent studied are comparable with those available in the literature and thus confirm the validity of the method used. Results of the RDFs analysis in the binary system studied show that the change of solution structure due to intermolecular hydrogen bonding plays a significant role in the solubility and nucleation of mefenamic acid polymorphs. A strong hydrogen bonding between solute-solvent and solute-solute in the solution have led to greater solubility values and different polymorphic form of mefenamic acid crystals.